2021
DOI: 10.3390/nano11071744
|View full text |Cite
|
Sign up to set email alerts
|

Security-Enhanced 3D Data Encryption Using a Degradable pH-Responsive Hydrogel

Abstract: Based on degradable pH-responsive hydrogel, we report on an enhanced three-dimensional data encryption security technique in which a pH value is used for information manipulation. Featuring three types of states upon the pH value variation, namely, shrinkage, expansion and degradation, the hydrogel renders a limited pH value window as the “key” for information decryption. The pH-dependent shrinkage-to-expansion conversion of the hydrogel leads to a threshold pH value for retrieving the recorded data, whilst th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our previous work demonstrated that hydrogel with high water‐swelling ratio in length >5 could provide an effective platform for laser‐printing information encryption. [ 44 ] Therefore, the high swelling ability of OS gel in water was another essential factor for the information encryption/decryption, which was obtained by the charge‐to‐charge repulsion of MPTAC groups in the hydrophilic PAM network. Upon being immersed in water, the charge‐to‐charge repulsion enabled the expansion of the hydrophilic PAM network, which allowed more water molecules to be absorbed into OS gel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work demonstrated that hydrogel with high water‐swelling ratio in length >5 could provide an effective platform for laser‐printing information encryption. [ 44 ] Therefore, the high swelling ability of OS gel in water was another essential factor for the information encryption/decryption, which was obtained by the charge‐to‐charge repulsion of MPTAC groups in the hydrophilic PAM network. Upon being immersed in water, the charge‐to‐charge repulsion enabled the expansion of the hydrophilic PAM network, which allowed more water molecules to be absorbed into OS gel.…”
Section: Resultsmentioning
confidence: 99%
“…This diffuse reflection‐induced decrypting mechanism was similar to that in our previous report. [ 44 ] Based on the HSV model, the brightness of laser‐cutting area was 30% under daylight and increased to 60% under strong white light, which meant that the information was not visible in daylight but visible in strong white light, leading to a cycle of encryption and decryption (Figure S18, Supporting Information). Therefore, OS gel could be used to create an optical‐switching gel system for multistage information encryption/decryption triggered by water swelling‐induced phase transition, which is expected to provide a new type of information‐storage platform with improved security.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Nanostructures and microstructures can be released from hydrogels when exposed to certain stimuli, such as temperature, pH, enzymes and magnetic fields. 75 , 76 …”
Section: The Design Strategy Of Biomembrane-based Nanostructure- and ...mentioning
confidence: 99%